Comprehensive Physiology 2015
DOI: 10.1002/cphy.c140016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stroke on the Autonomic Nervous System

Abstract: Stroke is the fourth leading cause of death in the United States and the second most common cause of death worldwide; stroke is also the leading cause of long-term disability worldwide. It is clear that the consequences of cerebral ischemia reach beyond the brain into the periphery, and a significant number of stroke related deaths are the result of conditions that develop poststroke in the periphery. The two leading causes of non-neurogenic death poststroke are cardiac abnormalities and infections. Changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 214 publications
0
64
0
3
Order By: Relevance
“…Beta‐blocker has been part of the antihypertension treatment arsenal for many years, but meta‐analyses have shown they are less effective than other agents in primary and secondary stroke prevention. Yet, BB may confer a benefit in stroke by mitigating the acute hyper activation of the sympathetic nervous system, which has been associated with adverse cardiovascular and immune effects …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta‐blocker has been part of the antihypertension treatment arsenal for many years, but meta‐analyses have shown they are less effective than other agents in primary and secondary stroke prevention. Yet, BB may confer a benefit in stroke by mitigating the acute hyper activation of the sympathetic nervous system, which has been associated with adverse cardiovascular and immune effects …”
Section: Discussionmentioning
confidence: 99%
“…Yet, BB may confer a benefit in stroke by mitigating the acute hyper activation of the sympathetic nervous system, which has been associated with adverse cardiovascular and immune effects. 22 Previous works addressed the relationship between survival and pre-stroke BB use, most of them using shorter follow-up periods. Two studies with a similar follow-up period showed results consistent with ours: Sykora and colleagues analyzed individual patient data from approximately 5200 ischemic stroke patients and found no difference in 3-month mortality by pre-stroke BB use.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the crosstalk between the acutely injured brain and the heart are not well understood at present. Current thinking is that cerebral ischaemia triggers an acute stress response that is mediated by the overactive sympathetic nervous system . However, the signalling pathways between the brain and the heart as well as the molecular downstream processes in the heart remain to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…[20] The ischemic brain can act through the autonomic nervous system to have suppressive effect that can induce intercurrent infections and contribute to the morbidity and mortality after stroke. [21][22][23] Therefore, immune system-mediated inflammation is critically involved in determining the fate of the brain following ischemic stroke. [24][25][26] Understanding the mechanisms underlying role of neuroinflammation in ischemic stroke would provide important targets for the development of therapy in ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%